2014
DOI: 10.1371/journal.pone.0099176
|View full text |Cite
|
Sign up to set email alerts
|

Interactome Profile of the Host Cellular Proteins and the Nonstructural Protein 2 of Porcine Reproductive and Respiratory Syndrome Virus

Abstract: The nonstructural protein 2 (NSP2) is considered to be one of crucial viral proteins in the replication and pathogenesis of porcine reproductive and respiratory syndrome virus (PRRSV). In the present study, the host cellular proteins that interact with the NSP2 of PRRSV were immunoprecipitated with anti-Myc antibody from the MARC-145 cells infected by a recombinant PRRSV with 3xMyc tag insertion in its NSP2-coding region, and then 285 cellular proteins interacting with NSP2 were identified by LC-MS/MS. The Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 72 publications
2
27
0
Order By: Relevance
“…The physical separation of the large cytoplasmic PLP2 protease domain and the luminal C-termini by the membrane interface would require that polyprotein processing of the nsp2 ↓ nsp3 junction to be cleaved either in trans following membrane insertion, or that cleavage of nsp2 ↓ nsp3 precedes membrane insertion. Similarly, current data supports both as possibilities; that the PLP2 exhibits both cis-and trans-cleavage activities (Han et al, 2009) and that nsp2 has been also shown to interact with cellular chaperones known to participate in post-translational membrane integration (Wang et al, 2014). Most simply, any nsp2 isoform resulting from a cleavage event between the PLP2 protease domain and the TM region would allow for physical separation of these domains and thus differential localization.…”
Section: Tablesupporting
confidence: 73%
See 1 more Smart Citation
“…The physical separation of the large cytoplasmic PLP2 protease domain and the luminal C-termini by the membrane interface would require that polyprotein processing of the nsp2 ↓ nsp3 junction to be cleaved either in trans following membrane insertion, or that cleavage of nsp2 ↓ nsp3 precedes membrane insertion. Similarly, current data supports both as possibilities; that the PLP2 exhibits both cis-and trans-cleavage activities (Han et al, 2009) and that nsp2 has been also shown to interact with cellular chaperones known to participate in post-translational membrane integration (Wang et al, 2014). Most simply, any nsp2 isoform resulting from a cleavage event between the PLP2 protease domain and the TM region would allow for physical separation of these domains and thus differential localization.…”
Section: Tablesupporting
confidence: 73%
“…Since strong viral proteinÀ protein interactions can complicate assessment of native transmembrane insertion (van der Meer et al, 1998), and additionally PRRSV nsp2 interacts with a wide range of cellular proteins (Wang et al, 2014), we chose to complete these initial studies on nsp2 transmembrane functionality within a reductionist cell-free translation system in the absence of all other viral proteins.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we see few binding host proteins and pathways identified later after this stage that emphasize the CP-induced cytopathic effect. In addition, cellular proteins and pathways, such as protein binding, translation, and apoptosis, targeted by CP NS3 are known to be targeted by other viruses, indicating common strategies among these viruses [17,35].…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al recently employed an IP approach combined with the LC-MS/MS to identify host cellular proteins that interact with PRRSV nsp2 [47]. Altogether, they identified 285 cellular proteins and selected two proteins to confirm these interactions.…”
Section: Discussionmentioning
confidence: 99%